(untitled) (The Journal of Plant Protection Sciences, 2020)
Mango is attacked by various insect pests among which mango shoot gall psylla Apsylla cistellata Bucton.(Psyllidae: Hemiptera) is the most important one in the district of Malda and Murshidabad, West Bengal. Adult females of the pest had been found to lay eggs at the sides of midribs during first week to end of March. Incubation period lasted from first week of March to middle of August. Eggs hatched in the middle of August and gall formation had been found to start from first week of September.